Effects of overnight fasting on working memory‐related brain network: An fMRI study. Issue 3 (12th November 2014) - Chechko, Natalia; Vocke, Sebastian; Habel, Ute; Toygar, Timur; Kuckartz, Lisa; Berthold‐Losleben, Mark; Laoutidis, Zacharias G.; Orfanos, Stelios; Wassenberg, Annette; Karges, Wölfram; Schneider, Frank; Kohn, Nils
Abstract Glucose metabolism serves as the central source of energy for the human brain. Little is known about the effects of blood glucose level (BGL) on higher‐order cognitive functions within a physiological range (e.g., after overnight fasting). In this randomized, placebo‐controlled, double blind study, we assessed the impact of overnight fasting (14h) on brain activation during a working memory task. We sought to mimic BGLs that occur naturally in healthy humans after overnight fasting. After standardized periods of food restriction, 40 (20 male) healthy participants were randomly assigned to receive either glucagon to balance the BGL or placebo (NaCl). A parametric fMRI paradigm, including 2‐back and 0‐back tasks, was used. Subclinically low BGL following overnight fasting was found to be linked to reduced involvement of the bilateral dorsal midline thalamus and the bilateral basal ganglia, suggesting high sensitivity of those regions to minimal changes in BGLs. Our results indicate that overnight fasting leads to physiologically low levels of glucose, impacting brain activation during working memory tasks even when there are no differences in cognitive performance. Hum Brain Mapp 36:839–851, 2015.© 2014 Wiley Periodicals, Inc.